Manganese potassium ore type carbon nano composite material as well as preparation method and application thereof

The manganite-type carbon nanocomposite synthesized by the hydrothermal method solves the problems of low capacity and complex potassium storage mechanism when graphite is used as an anode material for potassium ion batteries, realizes the dual functionality of the material, and improves the dynamic performance of the battery. and mass production advantages.

CN119349645APending Publication Date: 2025-01-24SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491279.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing graphite is used as the negative electrode material for potassium ion batteries, the capacity is low and cannot meet the needs of high energy density. At the same time, it will cause volume changes during the electrochemical reaction, complicating the potassium storage mechanism.

Method used

The manganese -potassium -type carbon nano composite material synthesized by water and thermal method can be used not only as a positive electrode material, but also used as a negative electrode material. Ultrasonic dispersed carbon nano -nanotubes and potassium permanganate in the dilute sulfuric acid solution, high temperature and high pressure reaction The fibrous structure with a multi -dimensional ion channel is formed after sintering.

Benefits of technology

This material can accelerate the transmission performance of potassium ions, improve the kinetic performance of the battery, enhance the rate performance and low-temperature performance, while simplifying the process flow, reducing costs, and having mass production advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349645A_ABST
    Figure CN119349645A_ABST
Patent Text Reader

Abstract

The invention provides a manganese potassium ore type carbon nano composite material as well as a preparation method and application thereof. The preparation method of the manganese potassium ore type carbon nano composite material comprises the following steps: preparing a dilute sulphuric acid solution, and adding a carbon nano tube into the dilute sulphuric acid solution for ultrasonic treatment to obtain a carbon nano tube solution; adding potassium permanganate, stirring, dispersing and uniformly mixing to obtain a mixed solution; putting the mixed solution into a high-pressure reactor, heating and reacting at high temperature, cooling, centrifuging and cleaning; and drying to obtain the manganese potassium ore type carbon nano composite material. The manganese potassium ore type carbon nano composite material synthesized through a hydrothermal method can be used as a positive electrode material and can also be used as a negative electrode material, the synthesis process is simple, and the great mass production advantage is achieved; the surface of the manganese potassium ore type carbon nano composite material presents a fibrous structure morphology, the manganese potassium ore type carbon nano composite material has a multi-dimensional ion channel, the transmission performance of potassium ions can be accelerated, the dynamic performance of a battery is further improved, and the battery developed by using the manganese potassium ore type carbon nano composite material as a battery material has better rate capability and low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of potassium ion batteries, and specifically relates to a cryptomelane-type carbon nanocomposite material and a preparation method and application thereof, in particular to an application of the cryptomelane-type carbon nanocomposite material in the preparation of potassium ion batteries as a double electrode material. Background Art

[0002] Lithium-ion batteries (LIBs) have achieved great success in electronic devices due to their high energy density and long cycle life. However, the global distribution of lithium resources is limited and uneven, especially domestic lithium mines are relatively scarce, most of which rely on imports, and the scarce lithium ore resources cannot meet the growing demand of these emerging applications. Sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) have similar electrochemical principles and are abundant in resources, and have more cost advantages in mass production. Compared with SIBs, PIBs have higher operating voltages and lower reduction potentials (K / K + The standard reduction potential is -2.93V; Na / Na + The standard reduction potential is -2.71V); the diffusion rate of potassium in carbon negative electrode materials is fast, and commercial graphite can be used as the negative electrode of potassium ion batteries; because the Lewis acidity of potassium is weak and the radius of solvated potassium ions is small, potassium ions have a faster migration speed.

[0003] Graphite is a promising negative electrode material for potassium ion batteries. It is abundant in resources, low in price, and has the advantages of excellent electrical conductivity, thermal conductivity and chemical stability. Potassium is an alkali metal element after lithium that can directly undergo an intercalation reaction with graphite. Potassium ions intercalated into graphite can generate KC8 compounds. The theoretical potassium storage capacity of graphite is 279mAh / g, which makes it possible to shift the focus of the mature graphite negative electrode industry from lithium-ion batteries to potassium-ion batteries. However, during the electrochemical reaction, when graphite is used as a negative electrode material for potassium ion batteries, it will cause some changes in volume; at the same time, because more carbon atoms are required to accommodate a larger volume of potassium, the potassium storage mechanism becomes more complicated. Therefore, in PIB, the capacity of graphite as a negative electrode material is low and cannot meet the market demand for high energy density.

[0004] For many years, an asymmetric configuration with two different electrode materials has been considered as the standard structure of rechargeable electrochemical devices (such as positive and negative electrode materials of LIB and SIB), while a symmetric battery using the same active material as the positive and negative electrodes will have greater commercial value. Therefore, it is urgent to provide a cryptomelane-type carbon nanocomposite with a dual-electrode system that can be used as both a positive electrode material and a negative electrode material in the preparation of potassium ion batteries. Summary of the invention

[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a cryptomelane-type carbon nanocomposite material; the second purpose of the present invention is to provide a cryptomelane-type carbon nanocomposite material prepared by the preparation method; the third purpose of the present invention is to provide a method for preparing a dual-electrode pole piece; the fourth purpose of the present invention is to provide a dual-electrode pole piece prepared by the preparation method; the fifth purpose of the present invention is to provide an application of a cryptomelane-type carbon nanocomposite material or a dual-electrode pole piece in the preparation of a potassium ion battery.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a cryptomelane-type carbon nanocomposite material, the preparation method comprising the following steps:

[0008] Step 1, preparing a dilute sulfuric acid solution, adding carbon nanotubes into the dilute sulfuric acid solution and performing ultrasonication to obtain a carbon nanotube solution; then adding potassium permanganate and stirring to disperse and mix to obtain a mixed solution;

[0009] Step 2: placing the mixed solution in a high-pressure reactor, heating at high temperature for reaction, centrifuging and washing after cooling; and drying to obtain cryptomelane-type carbon nanocomposite material.

[0010] Cryptomelane compounds are a type of MnO2 minerals with a molecular sieve structure constructed by a double chain of MnO6 octahedra with shared edges, forming a unique (2×2)+(1×1) tunnel. + , mixed valence Mn ions (Mn 4 + and a small amount of Mn 3+ ) exists in the center of the octahedron. At the same time, the manganese ions undergo multiple electron transfer reactions under different voltage windows. Therefore, this material is particularly suitable as a bifunctional electrode material for PIBs, in which K + The Mn ions can be reversibly inserted / extracted in one-dimensional (1D) tunnels accompanied by the redox process.

[0011] The cryptomelane-type carbon nanocomposite material synthesized by the hydrothermal method of the present invention can be used not only as a positive electrode material but also as a negative electrode material. During the preparation process, a slurry is synthesized that can be used for the positive and negative electrode material systems, which greatly shortens the process flow, process time and cost; the synthesis process is simple and has great advantages in mass production.

[0012] The cryptomelane-type carbon nanocomposite material prepared by the present invention has a fibrous structural morphology on its surface and has multidimensional ion channels, which can accelerate the transmission performance of potassium ions and further improve the kinetic performance of the battery. The battery developed using the cryptomelane-type carbon nanocomposite material has better rate performance and low-temperature performance.

[0013] The present invention uses a dilute sulfuric acid solution, which has a weak oxidizing property. During the reaction process of adding the dilute sulfuric acid solution, M 4+ Will be reduced to Mn 3+ Finally, after the reaction under high temperature and high pressure, K in the solution + , unreacted Mn 4+ and the Mn generated by the reaction 3+ Sintered in CNT material, the reactants are then washed to remove the unreacted K + , Mn 4+ and Mn 3+ , this contains Mn 3+ and Mn 4+ The material has a unique (2×2)+(1×1) tunnel structure, which contains K + , can be used as a cathode material, with a unique tunnel structure that can accommodate K + , so it can also be used as anode material. The XPS data of the product material shows that Mn in the product has two valence states.

[0014] In the above preparation method, preferably, in step 1, the concentration of the dilute sulfuric acid solution is 30-50 mM.

[0015] In the above preparation method, preferably, the concentrated sulfuric acid used to prepare the dilute sulfuric acid solution has a purity of AR grade 98% concentrated sulfuric acid.

[0016] In the above preparation method, preferably, in step 1, the ultrasonication time is 0.5 to 4 hours.

[0017] In the above preparation method, preferably, in step 1, the mass of the potassium permanganate is 2 to 4 times the mass of the carbon nanotubes.

[0018] In the above preparation method, preferably, in step 1, the stirring and dispersing process is carried out in a disperser, and the dispersing time is 20 to 60 minutes.

[0019] In the above preparation method, preferably, in step 2, the material of the high-pressure reactor is a corrosion-resistant Teflon lining material.

[0020] In the above preparation method, preferably, in step 2, the reaction temperature of the high-pressure reactor is 100-150° C., and the reaction time is 10-24 h.

[0021] In the above preparation method, preferably, in step 2, the cooled sample is first centrifuged, the supernatant is removed, deionized water is added and stirred evenly, and then centrifuged again to remove the supernatant, and the washing is repeated 3 to 8 times.

[0022] In the above preparation method, preferably, in step 2, a drying step is performed in an oven, and the drying temperature is 70 to 100° C. and the time is 10 to 24 hours.

[0023] On the other hand, the present invention also provides a cryptomelane-type carbon nanocomposite material, which is prepared by any of the preparation methods described above.

[0024] In another aspect, the present invention further provides a method for preparing a dual-electrode electrode sheet, the method comprising the following steps:

[0025] The cryptomelane-type carbon nanocomposite prepared by the above-mentioned preparation method or the cryptomelane-type carbon nanocomposite, conductive carbon black and polyvinylidene fluoride are added with N-methylpyrrolidone to adjust the solid content, and the mixture is dispersed at high speed to obtain a mixed slurry;

[0026] The mixed slurry is coated onto aluminum foil or copper foil using a scraper, and a dual motor pole piece is obtained after drying.

[0027] In the above preparation method, preferably, the mass ratio of the cryptomelane-type carbon nanocomposite material, the conductive carbon black and the polyvinylidene fluoride is 8:1:1.

[0028] In the above preparation method, preferably, N-methylpyrrolidone is added to adjust the solid content to 50% to 70%.

[0029] In the above-mentioned preparation method, preferably, the amount of active material (composite material on the sheet of buckle assembly) coated on the aluminum foil or copper foil by the mixed slurry is 1.5-2.5 mg.

[0030] On the other hand, the present invention also provides a dual-electrode pole piece, which is prepared by the above-mentioned preparation method; wherein, the dual-electrode pole piece prepared by applying the mixed slurry on aluminum foil can be used as a positive electrode pole piece; the dual-electrode pole piece prepared by applying the mixed slurry on copper foil can be used as a negative electrode pole piece.

[0031] On the other hand, the present invention also provides the cryptomelane-type carbon nanocomposite material prepared by the above-mentioned preparation method, or the cryptomelane-type carbon nanocomposite material, or the double electrode plate prepared by the above-mentioned preparation method, or the use of the double electrode plate in the preparation of potassium ion batteries.

[0032] Beneficial effects of the present invention:

[0033] (1) The cryptomelane-type carbon nanocomposite material synthesized by the hydrothermal method of the present invention can be used not only as a positive electrode material but also as a negative electrode material. During the preparation process, a slurry is synthesized that can be used in the positive and negative electrode material systems, which greatly shortens the process flow, process time and cost. The synthesis process is simple and has great advantages in mass production.

[0034] (2) The surface of the cryptomelane-type carbon nanocomposite prepared by the present invention presents a fibrous structure morphology and has multidimensional ion channels, which can accelerate the transmission performance of potassium ions and further improve the kinetic performance of the battery. The battery developed using the cryptomelane-type carbon nanocomposite as a battery material has better rate performance and low-temperature performance.

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a SEM comparison of the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1;

[0038] Figure 2 This is a comparison diagram of EDS mapping of the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1;

[0039] Figure 3 This is a comparison chart of the XPS valence state distribution of the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1;

[0040] Figure 4 A comparison of the electrochemical performance of potassium ion buckling prepared by using the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 as positive electrode materials;

[0041] Figure 5 This is a comparison chart of the electrochemical performance of potassium ion buckling prepared by using the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 as negative electrode materials. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.

[0043] Embodiment 1:

[0044] This embodiment provides a method for preparing a cryptomelane-type carbon nanocomposite material, the preparation method comprising the following steps:

[0045] (1) Use a 200 μL pipette to measure 142 μL of 98% concentrated H2SO4 solution, add it to 70 mL of deionized water, and mix on a mixer to obtain a 38 mM dilute H2SO4 solution;

[0046] (2) weighing 0.06 g of carbon nanotubes (CNT) and adding them to the above solution, and then dispersing the sample by ultrasonication for 1 h to obtain a carbon nanotube solution;

[0047] (3) adding 0.18 g of KMnO4 powder to the carbon nanotube solution obtained in step (2), stirring in a disperser for 20 min to allow KMnO4 to fully dissolve in the solution, and mixing to obtain a mixed solution;

[0048] (4) placing the mixed solution obtained in step (3) into a stainless steel high-pressure reactor lined with Teflon, performing a high-temperature hydrothermal reaction at 120° C. for 24 h, and then cooling the sample;

[0049] (5) The cooled sample was centrifuged to remove the supernatant, then 70 mL of deionized water was added for washing, and the supernatant was removed by centrifugation again. After repeated washing for 3 times, the sample was placed in an oven at 80 °C and dried for 12 h to obtain the target product KMO / CNT nanocomposite material, referred to as KMO / CNT-30.

[0050] This embodiment also provides a method for preparing a dual-electrode electrode sheet using the cryptomelane-type carbon nanocomposite material (KMO / CNT-30) prepared above. The specific preparation method is as follows:

[0051] (1) 10 g of the KMO / CNT-30 composite material, conductive carbon black (SP) and polyvinylidene fluoride (PVDF) prepared in the above embodiment were weighed in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added for dispersion and the solid content was adjusted to 60%, and then the mixture was dispersed at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry;

[0052] (2) The mixed slurry is coated on aluminum foil with a 200 μm scraper, and then dried in a 110° C. air drying oven for 1 hour and taken out to obtain a positive electrode sheet; alternatively, the mixed slurry is coated on copper foil with a 200 μm scraper, and then dried in a 110° C. air drying oven for 1 hour and taken out to obtain a negative electrode sheet.

[0053] This embodiment also provides a potassium ion button battery, which uses the positive electrode sheet or negative electrode sheet prepared above, and the specific assembly method is as follows:

[0054] (1) Cut the electrode into 12 mm small discs, compact, slice and vacuum dry them in accordance with the procedure of button cell assembly, and then assemble them into CR2032 type half-cell button cells in a glove box, wherein the diaphragm is made of glass fiber, the counter electrode is a 14 mm potassium sheet, and the glove box is an argon glove box with a water content of <1 ppm and an oxygen content of <1 ppm; add electrolyte during the assembly process, and use a 1M KPF6 solution with a volume ratio of carbonate: diethyl carbonate: propylene carbonate (EC: DEC: PC) of 1:1:1 for injection; in the positive electrode assembly process, the sodium sheet is used as the negative electrode, and the above-prepared positive electrode sheet is used as the positive electrode; in the negative electrode assembly process, the sodium sheet is used as the positive electrode, and the above-prepared negative electrode sheet is used as the negative electrode;

[0055] (2) The assembled buckle battery is sealed and activated at 35° C. for 12 h to prepare a potassium ion buckle battery.

[0056] Comparative Example 1:

[0057] This comparative example provides a method for preparing cryptomelane-type material, which comprises the following steps:

[0058] (1) Use a 200 μL pipette to measure 142 μL of 98% concentrated H2SO4 solution, add it to 70 mL of deionized water, and mix on a mixer to obtain a 38 mM dilute H2SO4 solution;

[0059] (2) Weigh 0.18 g of KMnO4 powder and add it to the above dilute sulfuric acid solution, and stir in a disperser for 20 min to allow KMnO4 to fully dissolve in the solution to obtain a potassium permanganate solution;

[0060] (3) placing the potassium permanganate solution obtained in step (2) into a stainless steel high-pressure reactor lined with Teflon, performing a high-temperature hydrothermal reaction at 120° C. for 24 h, and then cooling the sample;

[0061] (4) The cooled sample was centrifuged to remove the supernatant, and then 70 mL of deionized water was added for washing, and the supernatant was removed by centrifugation again. After repeated washing for 3 times, the sample was placed in an oven at 80° C. and dried for 12 h to obtain the target product, cryptomelane-type material, referred to as KMO.

[0062] This comparative example also provides a method for preparing a dual-electrode electrode sheet using the KMO material prepared above. The specific preparation method is as follows:

[0063] (1) 10 g of the KMO material, conductive carbon black (SP) and polyvinylidene fluoride (PVDF) prepared in the above embodiment were weighed in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added for dispersion and the solid content was adjusted to 60%, and then the mixture was dispersed at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry;

[0064] (2) The mixed slurry is coated on aluminum foil with a 200 μm scraper, and then dried in a 110° C. air drying oven for 1 hour and taken out to obtain a positive electrode sheet; alternatively, the mixed slurry is coated on copper foil with a 200 μm scraper, and then dried in a 110° C. air drying oven for 1 hour and taken out to obtain a negative electrode sheet.

[0065] This comparative example also provides a potassium ion button battery, which uses the positive electrode sheet or negative electrode sheet prepared above, and the specific assembly method is as follows:

[0066] (1) Cut the electrode into 12 mm small discs, compact, slice and vacuum dry them in accordance with the procedure of button cell assembly, and then assemble them into CR2032 type half-cell button cells in a glove box, wherein the diaphragm is made of glass fiber, the counter electrode is a 14 mm potassium sheet, and the glove box is an argon glove box with a water content of <1 ppm and an oxygen content of <1 ppm; add electrolyte during the assembly process, and use a 1M KPF6 solution with a volume ratio of carbonate: diethyl carbonate: propylene carbonate (EC: DEC: PC) of 1:1:1 for injection; in the positive electrode assembly process, the sodium sheet is used as the negative electrode, and the above-prepared positive electrode sheet is used as the positive electrode; in the negative electrode assembly process, the sodium sheet is used as the positive electrode, and the above-prepared negative electrode sheet is used as the negative electrode;

[0067] (2) The assembled buckle battery is sealed and activated at 35° C. for 12 h to prepare a potassium ion buckle battery.

[0068] Test experiment:

[0069] 1. Scanning electron microscope test experiment

[0070] The KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 were subjected to scanning electron microscopy test experiments. The experimental results are as follows: Figure 1 shown.

[0071] Depend on Figure 1 It can be seen that the original KMO shows a typical nanorod morphology with an average diameter of about 30nm and a length of up to 1μm. When the mass ratio of CNT is 30%, the KMO nanorods are evenly interwoven by CNTs to form an array structure of the KMO / CNT-30 sample.

[0072] 2. Energy dispersive X-ray experiment

[0073] The elemental composition and distribution of the surface or near-surface area of ​​the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 were analyzed by energy dispersive X-ray spectrometer. The experimental results are as follows: Figure 2 shown.

[0074] Depend on Figure 2 It can be seen that the EDS mapping image further verifies the existence and uniform distribution of K, Mn and O elements in the KMO matrix; K, Mn, O and C are evenly distributed in the EDS image of KMO / CNT-30, which further illustrates that a uniform nanohybrid is formed by entanglement of nanorods and nanotubes.

[0075] 3. X-ray photoelectron spectroscopy experiment

[0076] The XPS valence distribution diagram of the Mn element was analyzed by X-ray photoelectron spectrometer to detect the KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1. The experimental results are as follows: Figure 3 shown.

[0077] Depend on Figure 3 It can be seen that both material systems contain Mn 4+ and Mn 3+ Two valence states of elements.

[0078] 4. Potassium ion buckling electrochemical performance test

[0079] 4.1. Potassium ion buckling test as positive electrode

[0080] The KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 were used as positive electrode materials to prepare potassium ion buckle electricity for performance testing. The specific test process is as follows:

[0081] Negative electrode: stand for 2h → discharge at rate 0.1C, voltage ≤0.005v → constant current discharge 0.05mA, voltage ≤0.005v → constant current discharge 0.02mA, voltage ≤0.005v → stand for 10min → charge at rate 0.1C, voltage ≥2V.

[0082] Positive electrode: let stand for 2h → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min

[0083] The experimental results are as follows Figure 4 As shown, Figure 4 (a) is a comparison chart of the capacity at different rates. Figure 4 (b) is a comparison chart of the capacity and efficiency of the cycle.

[0084] Depend on Figure 4 The experimental results show that: Figure 4 The electrochemical performance of all samples as positive electrodes was studied by constant current discharge-charge tests within the potential window of 1.5-4.0 V. Figure 4 a shows the average temperature of all samples between 10 and 500 mA. -1 The rate performance at different current densities. KMO / CNT-30 achieved the best rate capacity at 20, 50, 100, 200 and 500 mA / g, which were 206.2 mAh / g, 170.8 mAh / g, 132.5 mAh / g, 102.4 mAh / g and 66.7 mAh / g, respectively. KMO / CNT-30 also showed good cycle stability, providing higher initial capacity and efficiency. Figure 4 In b, at a current density of 100 mA / g, the discharge capacity of KMO / CNT-30 is 229.9 mAh / g, and after 25 cycles, the remaining capacity of KMO / CNT-30 remains at 136.7 mAh / g (25th time); in the bare KMO material, the first cycle capacity is 98.7 mAh / g and, after 25 cycles, the remaining capacity is 48.6 mAh / g. It can be clearly seen from the above data that KMO / CNT-30, as a positive electrode material, has better performance in capacity, efficiency and cycle performance.

[0085] 4.2. Potassium ion charge test as negative electrode

[0086] The KMO / CNT-30 composite material prepared in Example 1 and the KMO material prepared in Comparative Example 1 were used as negative electrode materials to prepare potassium ion buckle electricity for performance testing. The specific test process is as follows:

[0087] Negative electrode: stand for 2h → discharge at rate 0.1C, voltage ≤0.005v → constant current discharge 0.05mA, voltage ≤0.005v → constant current discharge 0.02mA, voltage ≤0.005v → stand for 10min → charge at rate 0.1C, voltage ≥2V.

[0088] Positive electrode: let stand for 2h → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min → constant voltage charge, current 0.005A cut off → constant current discharge 0.1C, voltage 2V cut off → let stand for 10min → rate charge 0.1C, voltage 4V cut off → let stand for 10min

[0089] The experimental results are as follows Figure 5 As shown, Figure 5 (a) is a comparison chart of the capacity at different rates. Figure 5 (b) is a comparison chart of the capacity and efficiency of the cycle.

[0090] Depend on Figure 5 The experimental results show that: Figure 5 a is the test of the rate performance advantage of nanocomposites as negative electrode materials at different current densities of 20-1000 mA / g. As can be seen from the figure, due to the enhanced electron transport capacity, KMO / CNT-30 exhibits excellent rate characteristics at 100, 200, 500 and 1000 mA g -1 The capacities under these conditions are 367.1, 306.4, 211.0 and 127.2 mAh / g, respectively, which are much higher than the rate performance of bare KMO material. Figure 5 b compares the cycling performance of KMO and KMO / CNT-30 at 50 mA / g. Obviously, after 250 cycles, the capacity of KMO decreases from 402.3 mAh / g in the first cycle to only 39.9 mAh / g after 250 cycles, and the capacity decay is serious. In contrast, KMO / CNT-30 can obtain a higher initial charge capacity (498.1 mAh / g) and extremely excellent cycling stability, and still has a high capacity retention rate of 380.5 mAh / g after 250 cycles.

[0091] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing cryptomelane-type carbon nanocomposite material, characterized in that: The preparation method comprises the following steps: Step 1, preparing a dilute sulfuric acid solution, adding carbon nanotubes into the dilute sulfuric acid solution and performing ultrasonication to obtain a carbon nanotube solution; then adding potassium permanganate and stirring to disperse and mix to obtain a mixed solution; Step 2: placing the mixed solution in a high-pressure reactor, heating at high temperature for reaction, centrifuging and washing after cooling; and drying to obtain cryptomelane-type carbon nanocomposite material.

2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the dilute sulfuric acid solution is 30-50 mM; Preferably, the concentrated sulfuric acid used to prepare the dilute sulfuric acid solution has a purity of AR grade concentrated sulfuric acid with a concentration of 98%.

3. The preparation method according to claim 1, characterized in that: In step 1, the ultrasonication time is 0.5 to 4 hours.

4. The preparation method according to claim 1, characterized in that: In step 1, the mass of the potassium permanganate is 2 to 4 times the mass of the carbon nanotubes; Preferably, in step 1, the stirring and dispersing process is carried out in a disperser, and the dispersing time is 20 to 60 minutes.

5. The preparation method according to claim 1, characterized in that: In step 2, the material of the high-pressure reactor is a corrosion-resistant Teflon lining material; Preferably, in step 2, the reaction temperature of the high-pressure reactor is 100-150° C., and the reaction time is 10-24 h.

6. The preparation method according to claim 1, characterized in that: In step 2, the cooled sample is first centrifuged, the supernatant is removed, deionized water is added and stirred evenly, and then centrifuged again to remove the supernatant, and the washing is repeated 3 to 8 times; Preferably, in step 2, a drying step is performed in an oven at a temperature of 70 to 100° C. for 10 to 24 hours.

7. A cryptomelane-type carbon nanocomposite material, which is prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing a dual-electrode pole piece, characterized in that: The preparation method comprises the following steps: The cryptomelane-type carbon nanocomposite prepared by the preparation method according to any one of claims 1 to 6 or the cryptomelane-type carbon nanocomposite according to claim 7, conductive carbon black and polyvinylidene fluoride, N-methylpyrrolidone is added to adjust the solid content, and high-speed dispersion is performed to obtain a mixed slurry; The mixed slurry is coated onto aluminum foil or copper foil using a scraper, and after drying, a dual motor pole piece is obtained; Preferably, the mass ratio of the cryptomelane-type carbon nanocomposite material, the conductive carbon black and the polyvinylidene fluoride is 8:1:1; Preferably, N-methylpyrrolidone is added to adjust the solid content to 50% to 70%; Preferably, the amount of active material coated on the aluminum foil or copper foil by the mixed slurry is 1.5 to 2.5 mg.

9. A dual-electrode electrode sheet, which is prepared by the preparation method according to claim 8; wherein: The double electrode sheet prepared by coating the mixed slurry on aluminum foil can be used as a positive electrode sheet; the double electrode sheet prepared by coating the mixed slurry on copper foil can be used as a negative electrode sheet.

10. Use of the cryptomelane-type carbon nanocomposite material prepared by the preparation method according to any one of claims 1 to 6, the cryptomelane-type carbon nanocomposite material according to claim 7, the double electrode sheet prepared by the preparation method according to claim 8, or the double electrode sheet according to claim 9 in the preparation of potassium ion batteries.